2022
DOI: 10.3390/ijerph19116389
|View full text |Cite
|
Sign up to set email alerts
|

Re-Developing the Adversity Response Profile for Chinese University Students

Abstract: Adversity response is fundamental to dealing with adversity. This paper reports the re-development and subsequent psychometric evaluation of the Adversity Response Profile for Chinese University Students (ARP-CUS). The data were collected from a Chinese university student sample (n = 474). Factor analysis and Rasch analysis were used to examine the psychometric properties of the ARP-CUS. Exploratory factor analysis revealed a six-factor model; then confirmatory factor analysis supported a five-factor solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, the discriminant validity was identified by the comparison of the square root of the AVE and the correlations between the three dimensions, where a value of the square root of AVE higher than the correlation coefficient indicated a good discriminant validity between different dimensions [47]. Furthermore, most researchers apply Rasch analysis for examining instrument quality and it has been suggested that using factor analysis and Rasch analysis can evaluate instrument quality more comprehensively [48][49][50][51]. Thus, we conducted multidimensional Rasch modeling, performed in ConQuest 2.0 (ACER, Victoria, Australia), due to the MMHLS being a multidimensional construct.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the discriminant validity was identified by the comparison of the square root of the AVE and the correlations between the three dimensions, where a value of the square root of AVE higher than the correlation coefficient indicated a good discriminant validity between different dimensions [47]. Furthermore, most researchers apply Rasch analysis for examining instrument quality and it has been suggested that using factor analysis and Rasch analysis can evaluate instrument quality more comprehensively [48][49][50][51]. Thus, we conducted multidimensional Rasch modeling, performed in ConQuest 2.0 (ACER, Victoria, Australia), due to the MMHLS being a multidimensional construct.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the use of the Conquest program is preferred in studies where multidimensional structures are examined or many-facet models are used (Bartolomé & Garaizar, 2022;Mendoza et al, 2022;Wang et al, 2022;Zhai, 2022).…”
Section: Gui Version Cmd Versionmentioning
confidence: 99%
“…Ownership is the degree to which people accept personal accountability for enhancing their current circumstances. Reach refers to the extent to which adversity might spread into other spheres of life and endurance implies the perception of how long adversity will last (Wang et al, 2022;Biswas & Banerjee, 2020;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%